Karbonasi Pelepah Sawit - Yemita, Sylvia; Helwani, Zuchra; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm fronds only used as a source of raw materials for animal feed, compost and organic fertilizer in the garden area so far. The heating value of palm fronds is 17.200 kJ/kg. The heating value can be improved by conducting carbonization process. Carbonization is a method to process biomass into solid fuel without oxygen where the temperature range is between 400-600 °C. The aim of this study is to produce a solid fuel from palm fronds by using carbonization process, to know the characteristics of products and to see the influence of reaction temperature, carbonization time and particle size of product towards heating value and volatile matter content. Carbonization temperature used were 400, 500, 600oC, carbonization time used were 90, 120, 150 minutes, and particle size used were 2, 4, 6 cm. Processing data in this study was conducted by Response Surface Methodology (RSM) by using Design Expert 7.0.0 program which is experimental design determined by Central Composite Design (CCD). The highest result of heating value was 28.469 kJ/kg at 400oC for 150 minutes and particle size 2 cm. The highest result of volatile matter content was 21,14 %-wt at 670oC for 120 minutes and particle size 4 cm. Significant process condition affecting the heating value was temperature and carbonization time. However, the condition affecting the volatile matter content were carbonization temperature, carbonization time and particle size.Keywords: Carbonization, Heating Value, Palm Frond, Volatile Matter.